تقييم وضع المياه الجوفية في محلة السواوة - مصراتة سنة 2021 وتأثيراتها البيئية باستخدام نظم المعلومات الجغرافية - فاطمة صالح إبشير; علي مصطفى سليم (The Libyan Journal of Science, 2024)
The research aims to assess the current status of groundwater properties in Al-Sawawah area. The Mahjoub-Misurata Area in the years 2021, based on the results of Ph. Electrical conductivity (EC), total dissolved salts (TDS), and some negative and positive ions of 13 groundwater samples. In addition, geographic database is built to produce digital maps using Arc GIS10.8. The results show a spatial discrepancy in the distribution of the qualitative characteristics of groundwater, where the pH values ​​ranged between 6.94 and 7.50, while the values ​​of the total dissolved salts were between 4556 and about 1198 mg/L. These values, the groundwater exceed the permissible limits according to the Libyan and international specifications for different use, especially domestic and agricultural uses. Furthermore, the electrical conductivity values range between 1788 and 6800, and the water was very hard according to the Todd classification, where the total hardness exceeded 301 mg/L, and the concentrations of calcium in groundwater wells were between 120 and 400 mg /L. The average chloride was recorded between 532.5 and 1881.5 mg/L with the evident indicators of agricultural land degradation and desertification. The study produced digital maps showing the geographical distribution of the groundwater properties and its spatial difference in Al-Sawawah locality.